2011
DOI: 10.1002/iub.421
|View full text |Cite
|
Sign up to set email alerts
|

Heparin plays a key regulatory role via a p53/FAK‐dependent signaling in melanoma cell adhesion and migration

Abstract: SummaryHeparin and its various derivatives affect cancer progression in humans. In this study, we show that heparin uptaken intracellularly by melanoma cells activated a signaling cascade, which in turn inhibited melanoma cell adhesion and migration. The reduced ability of M5 cells to adhere onto the fibronectin (FN) substrate was directly correlated to a decrease in the expression of focal adhesion kinase (FAK), which is a key regulator of melanoma motility. Cell treatment with heparin caused a marked downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
14
0
5
Order By: Relevance
“…4C). This finding suggests that heparin does not influence migration speed through changes in FN conformation, but needs to be present in the medium to be effective 38 , perhaps by acting intracellularly as previously suggested 46 . Interestingly, a closer look at the effects of soluble Hep2 and heparin on adhesion cluster formation revealed differences: a considerable reduction in the fraction of cells presenting polarized protrusions was noted in presence of soluble heparin, but not of soluble Hep2 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 63%
“…4C). This finding suggests that heparin does not influence migration speed through changes in FN conformation, but needs to be present in the medium to be effective 38 , perhaps by acting intracellularly as previously suggested 46 . Interestingly, a closer look at the effects of soluble Hep2 and heparin on adhesion cluster formation revealed differences: a considerable reduction in the fraction of cells presenting polarized protrusions was noted in presence of soluble heparin, but not of soluble Hep2 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 63%
“…Macrophages possibly add fuel to the fire bringing greater quantities of VEGF to the tumour site setting up new VEGF gradients favoring tumour growth, which in turn may upregulate MMPs and therefore metastatic behaviour. Heparin-treated tumour cells demonstrate reduced cell adhesion and migration [86], and given that heparin-binding sites are spliced during synthesis of VEGF isoforms, investigating how heparin may affect the efficacy of VEGF isoforms on tumour growth in vitro would be intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the putative participation of FAK signaling on the IGF-I-/EGF-dependent adhesion, we transfected MCF-7 cells with FAK siRNA (siFAK) designed according to Hong et al, (2006) [44] and demonstrated to be specific for the FAK gene [45]. As shown in Figs.…”
Section: Igf-i-/egf-induced Increase In Breast Cancer Cell Adhesion Dmentioning
confidence: 99%
“…siRNA MCF-7 cells in suitable dilution plated in T25 flasks in serum and antibiotics free DMEM, and incubated with siRNA (100 nM) sequences specific for the FAK [44,45]and IGF-IR gene (ON-TARGET plus SMART pool siRNA by Dharmacon)and with siRNA negative control sequences (siscramble). Specific siRNA (Invitrogen) and Lipofectamine TM 2000 (Invitrogen) (1μl/50μl medium) were added to Opti-MEM © (Invitrogen) for 5min at room temperature.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%